Pengaruh Lingkungan Kerja Dan Stres Kerja Terhadap Kinerja Pegawai Di Dinas Perumahan Dan Kawasan Permukiman Kabupaten Mesuji - Polorina, Endang; Parela , Epi (Jurnal Bisnis, Manajemen dan Akuntansi, 2025)
In improving employee performance, one of the factors is paying attention to the work environment, be it the physical work environment or the non-physical work environment. Another factor that influences performance is work stress. Stress is a condition that puts pressure on a person's self and soul beyond the limits of their abilities. An employee who is stressed will have a bad impact on his health and disrupt his work. The problem with work stress in this research is that stress due to pressure from organizational targets is also often experienced by employees so that it disrupts the work situation and there is less concentration in completing their tasks and there are some employees who are less skilled at their work so they don't know what they want to do which puts pressure on them. increase. This research aims to determine the influence of organizational culture and work environment on employee performance at Dinas Perumahan dan Kawasan Permukiman Kabupaten Mesuji.The type of research used in this research is quantitative field research, namely research that emphasizes analysis of data in the form of numbers and the research examines real life in the field, in this case the object being studied. This research used 48 research respondents. Based on data analysis, a hypothetical answer has been found, namely as follows; There is an influence of the work environment (X1) on employee performance (Y), with an influence level of 31%. There is an influence of work stress (X2) on employee performance (Y) with an influence level of 17.5%. There is an influence of the work environment (X1) and work stress (X2) together on employee performance (Y) with an influence level of 42.5%.